The Implementation of Case Study Model in Social Studies Learning to Enhance Students’ Conceptual Understanding at Public Junior High Schools in Makassar - A, Darmawati; Thahir, Mustain; Mana, Rivai; Usman, Nur Afdhalia; Salam, Supardi (International Journal of Education, Vocational and Social Science, 2025)
This study investigates the implementation of the case study model in Social Studies learning at public junior high schools in Makassar, focusing on its impact on students’ conceptual understanding. Using a qualitative case study design, data were collected through classroom observations, semi-structured interviews with two teachers and 60 students, and analysis of student worksheets and reflective journals. The findings reveal that teachers applied the case study model by integrating real-life local issues, such as urban flooding and waste management, into classroom instruction. This approach successfully engaged students in active inquiry, group discussions, and reflective analysis. Students reported higher motivation and found Social Studies more relevant to their daily lives, while teachers observed improvements in students’ analytical reasoning and ability to connect abstract concepts with real-world contexts. The analysis also showed that 38% of students achieved a high level of integrated conceptual understanding, moving beyond memorization to application and evaluation. Despite challenges related to time management and unequal group participation, the benefits of case-based learning outweighed its limitations. The study concludes that the case study model aligns with the Merdeka Belajar curriculum and constructivist principles, offering an effective strategy to foster deeper learning, civic awareness, and critical thinking in Social Studies classrooms in Indonesia.